Insulin resistance: the conflict between biological settings of energy metabolism and human lifestyle (a glance at the problem from evolutionary viewpoint) - Vladimir Nicolaevich Titov; Vladimir Pavlovich Shirinsky (Сахарный диабет)
A biological function of the phylogenetically late humoral mediator insulin is to provide energy substrates for locomotion, i.e. movement resulting from contraction of striated muscles. Insulin is able to meet this evolutionary demand of an organism by means of the effective ATP production in the mitochondria. Exogenous fatty acids, optimised endogenous fatty acids produced from glucose and glucose itself are the major substrates for ATP synthesis. Cells stimulated by insulin produce ω-9 С18:1 oleic acid from glucose. This fatty acid is oxidised by the mitochondria at a higher rate than exogenous and endogenous C16:0 palmitic fatty acid. In the normal state of insulin system and mitochondria, the frequent cause of insulin resistance is the non-optimal properties of dietary fatty acids supplied for oxidation by the mitochondria. Dietary excess of saturated palmitic fatty acid over monogenic oleic fatty acid causes insulin resistance to develop. Insulin resistance syndrome is the condition of in vivo energy deficiency and insufficient production of ATP for the realisation of the biological adaptation and compensation. Insulin effectively inhibits lipolysis only in phylogenetically late subcutaneous adipocytes but not in phylogenetically early visceral fat cells of the omentum. Discrepancy in the regulation of energy substrate metabolism against the background of a ‘relative biological perfection’ of higher mammals is the aetiological basis of insulin resistance.